Impact of audit assurance on the quality of sustainability reporting - Alexander Grommes (Junior Management Science (JUMS), 2025)
The subject of sustainability reporting is becoming increasingly important. In consequence of the implementation of the Corporate Sustainability Reporting Directive, a substantial number of companies will be required to have their sustainability reports audited beginning from financial year 2024. This paper examines the influence of external assurance on the quality of those sustainability reports. Therefore, the reports of all DAX and MDAX companies for financial year 2022 are examined using a novel textual analysis approach, to determine the individual report quality. The results demonstrate that there is no statistically significant relationship between assurance level and the quality of sustainability reports. Conversely, it was found that companies that are acting sustainable disclose a higher quantity of information and are more likely to demand voluntary assurance of their reports. These findings offer insights into the implications of assurance on sustainability reporting. Furthermore, the detailed overview of traditional and state-of-the-art textual analysis methods offers researchers a valuable resource for identifying the most appropriate methods to address their individual research questions.
Keywords: 650; audit assurance; CSRD; natural language processing; sustainability reporting; textual analysis